ELECTRONIC MONEY IN PERU: WHY IS IT IMPORTANT IN FINANCIAL INCLUSION? - Rodríguez Cairo, Vladimir (2014)
This article seeks to answer the question: Why is it important electronic money in the process of finan-cial inclusion in Peru?. According to data from the Superintendence of Banking and Insurance (SBS), as of June 2013, 57.3% of districts in the country lack access to the financial system. Due to this problem, it is necessary to institutionalize the policy of financial included, so that access and use of quality financial services by all segments of the population is promoted. An important step in this way, is the instrumentation of electronic money.From this perspective, for a better understanding of the subject, the content is structured in four parts. The first covers the history of both the current situation of the Peruvian financial system as the policy guideline. In the second the validity of electronic money is raised. The third covers the electronic money in Peru. The fourth analyzes the electronic money as a means of financial inclusion. Finally, conclusions are presented and disclosed the references.